2018
DOI: 10.1101/325464
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex-specific impact of patterns of imageable tumor growth on survival of primary glioblastoma patients

Abstract: ; 2 Purpose: Patient sex is recognized as a significant determinant of outcome but the relative prognostic importance of molecular, imaging, and other clinical features of GBM has not yet been thoroughly explored for male versus female patients. Combining multimodal MR images and patient clinical information, this investigation assesses which pretreatment MRIbased and clinical variables impact sexspecific survivorship in glioblastoma patients. Methods:We considered the multimodal MRI and clinical data of 494 p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Our research group has already completed a number of preliminary analyses on our ES cohort. Using biomathematical models, we found that extreme survivors have lower rates of image-based estimates of tumor cell proliferation than their shorter-surviving counterparts 39 . Additionally, a review of our cohort found the occurrence of giant cell morphology is higher among our ES patients (17.8%) (S.K.…”
Section: Preliminary Results From Analysis Of Our Extreme Survivorsmentioning
confidence: 92%
“…Our research group has already completed a number of preliminary analyses on our ES cohort. Using biomathematical models, we found that extreme survivors have lower rates of image-based estimates of tumor cell proliferation than their shorter-surviving counterparts 39 . Additionally, a review of our cohort found the occurrence of giant cell morphology is higher among our ES patients (17.8%) (S.K.…”
Section: Preliminary Results From Analysis Of Our Extreme Survivorsmentioning
confidence: 92%
“…This could reduce the computational expense and potentially lead to more accurate predictions. Finally, recent works [18,44] have noted differences in gliomas based on patient sex and have called for the inclusion of this information in analysis. For our work, it would be interesting to observe the differences in parameter predictions for male and female patients, though this would require a much larger dataset than we have used in order to be meaningful.…”
Section: Discussionmentioning
confidence: 99%
“…136 Two studies have used segmented MR imaging to find sex differences in tumor volume with mixed results, 137,138 while another study found that these volumes have a sex-specific impact on overall survival. 139 Taken together, these studies emphasize the need to consider sex differences in studies of glioma genetics and neuroimaging, particularly in the growing field of radiomics.…”
Section: Other Observed Sex Differences In Gliomamentioning
confidence: 99%